STRATEGI PENGEMBANGAN OBJEK WISATA SARASAH TANGKHUGAN DI NAGARI SALAREH AIA KECAMATAN PALEMBAYAN KABUPATEN AGAM - Maharani, Siska; Rahmanelli, Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to determine the development strategy for the Sarasah Tangkhugan waterfall tourist attraction in Nagari Salareh Aia, Palebayan District, Agam Regency. This type of research is descriptive qualitative. The informants in this study were Wali Nagari Palembayan and visitors. Data collection techniques in this study are observation, interviews, and documentation. The data analysis technique in this study uses the SWOT analysis method. This tourism object has the potential to develop because its beauty and panorama can attract tourists. The results of the research on the development strategy for the Sarasah Tangkhugan waterfall tourism object in Nagari Salareh Aia, Palembayan District, Agam Regency, it can be concluded that the local party needs to add facilities around the tourist attraction, pave unpaved roads, and make entrance gates so that it becomes a better tourist attraction for visiting tourists. Keywords: Development strategy, Tourist attraction, Sarasah Tangkhugan